Linear model to estimate the degradation index on the processing of recycled polypropylene due to the addition of stabilizer (2016)
In the present research work, a lineal model to estimate the Processing Degradation Index (PDI) of polypropylene from recycled industrial waste and municipal solid waste is presented. According to the previous thing an experimental design was done with two types of residue changing the additive stabilizer from 0.1 % to 0.6 % and obtaining in every case a Processing Degradation Index with which it was possible to construct the linear model. Finally, it was established that the observed relationship of multiple extrusions and the processing degradation index shows that in the case of industrial waste is less compared to wastes from landfills using the same levels of stabilizing additives, and is also observed ranging from 0.05% to 0.60% levels of additives required to optimize the blocking of degradation with the latter being the optimal concentration of additive to minimize the Processing Degradation Index. © 2016, Universidad de Tarapaca. All rights reserved.